Let's solve the equation step by step. The equation is:
\[ -2(3x - 15) - 4 = 56 \]
- Distribute \(-2\) to the terms inside the parentheses:
\[ -2 \cdot 3x + -2 \cdot -15 - 4 = 56 \]
This simplifies to:
\[ -6x + 30 - 4 = 56 \]
- Combine the constant terms \(30\) and \(-4\):
\[ -6x + 26 = 56 \]
- Subtract \(26\) from both sides to isolate the term with \(x\):
\[ -6x = 56 - 26 \]
This simplifies to:
\[ -6x = 30 \]
- Divide both sides by \(-6\) to solve for \(x\):
\[ x = \frac{30}{-6} \]
This simplifies to:
\[ x = -5 \]
So the solution is:
\[ \boxed{-5} \]